Analisis Work Engagement di Perusahaan Kelapa sawit - Theofilia Jade Oroh; I Nyoman Sutapa (Jurnal Titra, 2021)
PT. X is a company engaged in the oil industry. The oil produced is palm oil. This palm oil company has been established since 1970, but in February 2021 it was acquired. PT. X is currently focusing on innovating new products that will be launched in the near future. The product launch also coincided with the high demand for palm oil starting in October as much as 23.5% compared to the previous month. The company realizes that employee performance needs to be maximized considering the increasing demands of work. Companies want to know whether employees are ready for many demands by looking at the employee's attachment to the company. Company engagement can be measured by several factors, namely work demands, company support, and support from each individual. Questionnaires were distributed to collect data to all employees from various divisions in the company. The conclusion obtained is that job resources and personal resources have an impact on company employees. This impact is a good thing considering that the high job resources compared to job demand has a positive impact on the possibility of employees experiencing burnout or leaving their jobs to be small.